2022
DOI: 10.3390/ijfs10020042
|View full text |Cite
|
Sign up to set email alerts
|

Innovation Capabilities in the Banking Sector Post-COVID-19 Period: The Moderating Role of Corporate Governance in an Emerging Country

Abstract: The COVID-19 pandemic is damaging economies across the world, including financial markets and institutions in all possible dimensions. For banks in particular, the pandemic generates multifaceted crises. This is likely to be worse in developing economies with poor financial market architecture. Innovation is considered an important factor in organizational effectiveness and competitive advantage post-COVID-19. Understanding how the banking system can improve their innovation capabilities is an unsolved questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Innovation was important for banks to respond to COVID-19, which combined both knowledge management and business strategy and affected innovation capabilities (Kien and That 2022). Similarly, Edeh et al (2022) proposed that knowledge management had an important impact on innovation in the banking industry.…”
Section: Innovation and Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Innovation was important for banks to respond to COVID-19, which combined both knowledge management and business strategy and affected innovation capabilities (Kien and That 2022). Similarly, Edeh et al (2022) proposed that knowledge management had an important impact on innovation in the banking industry.…”
Section: Innovation and Transformationmentioning
confidence: 99%
“…In addition, the corporate governance mechanism was thought to be effective in improving the financial performance of banks during the pandemic (El-Chaarani et al 2022). Therefore, corporate governance had been regarded as the moderator of knowledge management, business strategy, and innovation capabilities, which are important to improving organizational effectiveness and competitiveness (Kien and That 2022). Furthermore, Kabbani et al (2022) suggested that banks should encourage leaders to strengthen suitable behaviors and attitudes to create an ethical culture and improve employees' willingness to get the COVID-19 vaccination.…”
Section: Introductionmentioning
confidence: 99%